A tubulin alpha 8 mouse knockout model indicates a likely role in spermatogenesis but not in brain development. - Diggle, C; Martinez-Garay, I; Molnar, Z; Brinkworth, M; White, E; Fowler, E; Hughes, R; Hayward, B; Carr, I; Watson, C; Crinnion, L; Asipu, A; et al. (Public Library of Science, 2017)
Tubulin alpha 8 (Tuba8) is the most divergent member of the highly conserved alpha tubulin family, and uniquely lacks two key post-translational modification sites. It is abundantly expressed in testis and muscle, with lower levels in the brain. We previously identified homozygous hypomorphic TUBA8 mutations in human subjects with a polymicrogyria (PMG) syndrome, suggesting its involvement in development of the cerebral cortex. We have now generated and characterized a Tuba8 knockout mouse model. Homozygous mice were confirmed to lack Tuba8 protein in the testis, but did not display PMG and appeared to be neurologically normal. In response to this finding, we re-analyzed the human PMG subjects using whole exome sequencing. This resulted in identification of an additional homozygous loss-of-function mutation in SNAP29, suggesting that SNAP29 deficiency, rather than TUBA8 deficiency, may underlie most or all of the neurodevelopmental anomalies in these subjects. Nonetheless, in the mouse brain, Tuba8 specifically localised to the cerebellar Purkinje cells, suggesting that the human mutations may affect or modify motor control. In the testis, Tuba8 localisation was cell-type specific. It was restricted to spermiogenesis with a strong acrosomal localization that was gradually replaced by cytoplasmic distribution and was absent from spermatozoa. Although the knockout mice were fertile, the localisation pattern indicated that Tuba8 may have a role in spermatid development during spermatogenesis, rather than as a component of the mature microtubule-rich flagellum itself.